Improving the means for intergovernmental communications in crisis - Landi, Dale M. (Dale Michael), 1938-; Augenstein, Bruno W.; Crain, C. M. (Cullen Malone), 1920-; Harris, William R. (William Robert), 1941-; Jenkins, Brian Michael; Rand eBooks (Santa Monica, CA : RAND, 1984)
This report summarizes assessments of potential bilateral and multilateral measures for enhancing superpower stability in times of nuclear crisis. Existing means for communication between the American and Soviet heads of state are less than adequate and could be substantially improved. Improved means for direct communication between the American and Soviet heads of state are not sufficient; the Hot Line should be supplemented by a link connecting the military command centers of the United States and the Soviet Union, and by improved links connecting each nation's capital with its embassy in the other's capital. Improved bilateral communication links between the United States and the Soviet Union are, by themselves, not sufficient; other countries should be interconnected with comparable systems. The United States should seek an agreement among nations to exchange information in the event of a nuclear crisis involving terrorist groups.
"June 1984."
Includes bibliographical references (p. 27-29).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Communication in international relations; Hotlines (International relations); Nuclear crisis control -- Soviet Union; Nuclear crisis control -- United States; Electronic books